Goncourt 2020 : mais qu’a-t-il de plus que les autres ? - Michel Bernard (Humanités Numériques)
Can we explain the successive choices of the académie Goncourt – which in 2020 led L’Anomalie by Hervé Le Tellier to win the Goncourt prize – on the basis of purely textual criteria? Using textometric tools on a corpus made up of the 15 novels of the first Goncourt selection and 32 other novels from the 2020 literary season, we will try to determine which lexical or stylistic markers can explain the four phases of selection. The final finding is negative, in the sense that none of the criteria identified has conclusive continuity over the four stages. This refers to the consideration of extra-textual characteristics for awarding the prize but also to the undecidability of the successive choices made by professional readers in the context of a negotiation.